The Performance of Nurses to Improve the Responsibility Quality of Nursing Services - Enok Sureskiarti; Mentari Mentari; Rusni Masnina; Milkhatun Milkhatun (Indonesian Journal of Global Health Research, 2020)
Responsiveness is a policy to assist and provide fast, responsive and precise service to customers, with clear information delivery. Each worker who provides any forms of service, prioritizes the aspect of service that greatly affects the behavior of the person who gets the service, so that the ability to respond from the employees to serve the community is in accordance with the level of absorption, understanding, and inconsistency in the various forms of service that he does not understand. Nursing Performance is a work achievement demonstrated by the executive nurse in carrying out the task of nursing care to produce a good output to the customer (organization, client, nurse themselves). This research aimed to determine the relationship of nurse performance in nursing care to the responsiveness quality of nursing service in RSIA Qurrata A'yun Samarinda. The study used a cross sectional approach. The validity and reliability tests were carried out on the nurses’ performance and the quality of service questionnaire which was carried out at RSIA Aisisyiah Samarinda to 30 patients. The instrument in this study used questionnaires with samples of 62 patients hospitalized, chosen with simple random sampling technique. The test analysis in this study used Chi-square test with P Value 0.000 < 0.05. It can be concluded that there is a significant relationship of nurse performance to the responsiveness quality of nursing service.